The North America of Juan B. Justo. A socialist view of United States in late XIX century - Romero, Juan Manuel (Historia y Comunicación Social, 2019)
This article presents some Argentine impressions of the United States in the late XIX century. In this paper, I analyze the chronicles that the young Juan B. Justo wrote during his trip to the United States in the mid 1895, and that were published by the recently started La vanguardia, the socialist’s paper. I intend to sow that Justo ideas belong to a broader context of discussions, and therefore share concerns with the views of contemporaries such as Ernesto Quesada a representative of the positivist culture.
Keywords: United States; Socialist press; Juan B. Justo; Ernesto Quesada.